Relación Entre La Duplicidad De La Marca Y La Penetración De La Marca En Productos De Consumo Habitual - Fischer, Laura; Espejo, Jorge (European Scientific Journal, ESJ, 2016)
In order to examine the association between a brand and its penetration for a series of everyday consumption products, a quantitative study was conducted on 60 households in Mexico City. During a 12 week time period the recurrent purchase behavior of participants was recorded and analyzed. Results revealed that a high percentage of participants who purchased a product identified with a specific Brand, also tended to purchase other products of the same Brand.